Family Planning Midwifery Care for Mrs. N Implant Acceptor with Oligomenorrea Problems at Bataraguru Health Center - Danita; Syastriani Isna Putri Syarif; Wa Ode Nurul Mutia , Wa Ode Nurul Mutia (International Journal of Multidisciplinary Learners, 2025)
Background: The Family Planning (KB) Program is a very important preventive health service for women and is an integral part of national development efforts.Objective:The ability of midwives to provide family planning assistance to implant recipients with oligomenorrhea problems at the Barataguru Health CenterSubject: The subjects selected were cases of implants with oligomenorrhea problems.Method:The research on midwifery care used was a case study, with Varney's 7-step midwifery management approach and SOAP.Results:The results of the subjective and objective data evaluation obtained Subjective data The mother said that she came to the health center for a consultation because she felt anxious and worried about her condition due to the long distance between menstrual cycles. indicating a diagnosis of implant contraception with oligomenorrhea problems. Objective data Weight before contraception: 65 kg Weight after contraception: 60 kg. Height of the mother: 163 cm Blood pressure: 120/80 mmHg. Pulse rate 98x / minute Temperature: 36.5 ⁰c Breathing: 20x / minute Analysis Diagnosis: Mrs. "N" with an implant contraception acceptor who feels stressed, anxious and worried about her condition because of her long menstrual cycles Conclusion: Midwifery services for Mrs. "N" who received a contraceptive implant who experienced stress, anxiety and worry due to her irregular menstrual cycles can be carried out properly. Actions taken include providing information on health status, advice on overcoming oligomenorrhea, psychological support and proper nutrition.Background: The Family Planning (KB) Program is a very important preventive health service for women and is an integral part of national development efforts.Objective:The ability of midwives to provide family planning assistance to implant recipients with oligomenorrhea problems at the Barataguru Health CenterSubject: The subjects selected were cases of implants with oligomenorrhea problems.Method:The research on midwifery care used was a case study, with Varney's 7-step midwifery management approach and SOAP.Results:The results of the subjective and objective data evaluation obtained Subjective data The mother said that she came to the health center for a consultation because she felt anxious and worried about her condition due to the long distance between menstrual cycles. indicating a diagnosis of implant contraception with oligomenorrhea problems. Objective data Weight before contraception: 65 kg Weight after contraception: 60 kg. Height of the mother: 163 cm Blood pressure: 120/80 mmHg. Pulse rate 98x / minute Temperature: 36.5 ⁰c Breathing: 20x / minute Analysis Diagnosis: Mrs. "N" with an implant contraception acceptor who feels stressed, anxious and worried about her condition because of her long menstrual cycles Conclusion: Midwifery services for Mrs. "N" who received a contraceptive implant who experienced stress, anxiety and worry due to her irregular menstrual cycles can be carried out properly. Actions taken include providing information on health status, advice on overcoming oligomenorrhea, psychological support and proper nutrition.